Blood culture isolates and antibiogram of Salmonella: Experience of a tertiary care hospital - Singh, Lavan (Med J Armed Forces India, 2016)
BACKGROUND: Enteric fevers contribute majorly to the burden of morbidity from infectious diseases in the developing world. Due to growing antibiotic resistance seen in their management, Salmonella and its various species are required to be periodically tested for sensitivity and resistance patterns, to guide the clinical management at the local level. This will also enable planning of antibiotic recycling wherever feasible. METHODS: A retrospective study of the results of blood culture isolates covering a period of 27 months was done at a tertiary care hospital. Blood samples were directly inoculated in Bactalert culture bottles and sub culture was done on Mac Conkey and Salmonella–Shigella Agar. Non-lactose fermenting colonies were processed for identification, antibiotic sensitivity and MIC value. Slide agglutination test using specific antisera was also done to confirm the serotype. Antimicrobial susceptibility was done in accordance with CLSI standards. RESULTS: 8413 blood samples were processed and 1027 (12.20%) were assessed as ‘culture positive’. Salmonella were isolated in 46 samples of which 38 (83%) were Salmonella typhi and a single isolate was Salmonella paratyphi B. S.typhi showed maximum sensitivity to imipenem (100%) (MIC <0.25 μg/ml) followed by ciprofloxacin (76.8%) (MIC >1 μg/ml) and nalidixic acid (50%) (MIC ≥ 32 μg/ml). S. paratyphi B showed 100% sensitivity to all the common antibiotics. Four samples (8%) were classified as multi drug resistant (MDR). CONCLUSION: Our study has shown improved sensitivity to ceftriaxone and cotrimoxazole. A high degree of susceptibility to ampicillin among both S. typhi and S.paratyphi A is encouraging. However, low susceptibility to nalidixic acid and ciprofloxacin is a cause for concern. There is a need for further clinical studies to evaluate the response to chloramphenicol in MDR cases and to formulate uniform laboratory guidelines to test antibiotic sensitivity of S. typhi isolates.